2020
DOI: 10.1101/2020.01.24.918995
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Peer review and preprint policies are unclear at most major journals

Abstract: Clear and findable publishing policies are important for authors to choose appropriate journals 15 for publication. We investigated the clarity of policies of 171 major academic journals across disciplines regarding peer review and preprinting. 31.6% of journals surveyed do not provide information on the type of peer review they use. Information on whether preprints can be posted or not is unclear in 39.2% of journals. 58.5% of journals offer no clear information on whether reviewer identities are revealed to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 33 publications
(34 reference statements)
2
11
0
1
Order By: Relevance
“…For example, in our sample, 18% of editors reported that reviewer anonymity was left at the reviewers' discretion. This estimate is consistent with findings from Klebel et al 2020 [27], and almost four-times higher than the highest estimate from Publons data in 2017 [29]. However, importantly we note this movement toward greater flexibility was somewhat overshadowed by the 39% of editors reporting that reviewers identifying themselves within a blinded framework would be grounds for editing the report without the reviewer's permission.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…For example, in our sample, 18% of editors reported that reviewer anonymity was left at the reviewers' discretion. This estimate is consistent with findings from Klebel et al 2020 [27], and almost four-times higher than the highest estimate from Publons data in 2017 [29]. However, importantly we note this movement toward greater flexibility was somewhat overshadowed by the 39% of editors reporting that reviewers identifying themselves within a blinded framework would be grounds for editing the report without the reviewer's permission.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, given that it is estimated that 10% of reviewers account for 50% of performed reviews, it is not surprising that the perceived impact of changes on an editor's ability to recruit reviewers contributes heavily to journal policymaking decisions [7]. It is therefore also not surprising for the reasons above that we note very low uptake of the three policies interactions in the current study and previous research [26,27,29].…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Variants of these processes also include zero-blind (neither reviewers nor authors are anonymous), single-blind (reviewers are anonymous), and double-blind (both authors and reviewers are anonymous) systems (see for example [4]). With the major changes *Correspondence: lonni.besancon@gmail.com Deceased 1 Linköping University, Norrköping, Sweden 2 Université Paris Sud, Orsay, France Full list of author information is available at the end of the article currently happening in scholarly communication systems, there is now a strong imperative for those who manage the peer review process to be absolutely clear about their policies and, where possible, upon what evidence such policies are based [5].…”
Section: Introductionmentioning
confidence: 99%